Spiritual Tourism as a Sustainable Education Model at Taman Beji Griya Waterfall Bali - I Gede Putu Sudirgayasa; I Nyoman Piartha; I Gusti Made Widya Sena (Institut Pariwisata dan Bisnis Internasional, 2026)
Spiritual tourism has evolved into a complex global phenomenon between popular culture and social media. This study aims to analyze the spiritual tourism of Taman Beji Griya Waterfall in Bali as a model of sustainability education. Using a qualitative method with a case study approach, this study dissects the implementation of the Tri Hita Karana philosophy which is integrated with Jack Mezirow's Transformative Learning Theory. The findings suggest that the management of these destinations has succeeded in creating a